Physicochemical and antibacterial properties of chitosan‐polyvinylpyrrolidone films containing self‐organized graphene oxide nanolayers. Issue 11 (1st December 2015) - Mahmoudi, Nafiseh; Ostadhossein, Fatemeh; Simchi, Abdolreza
ABSTRACT: Chitosan films have a great potential to be used for wound dressing and food‐packaging applications if their physicochemical properties including water vapor permeability, optical transparency, and hydrophilicity are tailored to practical demands. To address these points, in this study, chitosan (CS) was combined with polyvinylpyrrolidone (PVP) and graphene oxide (GO) nanosheets (with a thickness of ∼1 nm and lateral dimensions of few micrometers). Flexible and transparent films with a high antibacterial capacity were prepared by solvent casting methods. By controlling the evaporation rate of the utilized solvent (1 vol % acidic acid in deionized water), self‐organization of GO in the polymer matrix was observed. The addition of PVP to the CS/GO films significantly increased their water vapor permeability and optical transmittance. A blue shift in the optical absorption edge was also noticed. Thermal analysis coupled with Fourier transform infrared spectroscopy suggested that the superior thermal stability of the nanocomposite films was due to the formation of hydrogen bonds between the functional groups of chitosan with those of the graphene oxide. An improved bactericidal capacity of the nanocomposite films against gram‐positive Staphylococcus aureus and gram‐negative Escherichia coli bacteria was also observed. Highly flexible, transparent (opacity of 6.95), and antimicrobial CS/25 vol % PVP/1 wt % GO films were prepared. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43194. Abstract :